2021
DOI: 10.1159/000517469
|View full text |Cite
|
Sign up to set email alerts
|

Renal Resistive Index as a Predictor of Acute Kidney Injury and Mortality in COVID-19 Critically Ill Patients

Abstract: <b><i>Background:</i></b> Acute kidney injury (AKI) in patients with COVID-19 can be caused by multiple mechanisms. Renal resistive index (RRI) is a noninvasive instrument to evaluate kidney hemodynamics, and it is obtained by analysis of intrarenal arterial waves using Doppler ultrasound. This study aimed to determine the role of RRI in predicting AKI and adverse outcomes in critically ill patients with COVID-19. <b><i>Methods:</i></b> This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
2
6
1
Order By: Relevance
“…It is also important to note that our study replicates the findings of an increased risk of developing acute kidney injury and increased total days of hospitalization, as reported in previous studies in other populations 17,19 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is also important to note that our study replicates the findings of an increased risk of developing acute kidney injury and increased total days of hospitalization, as reported in previous studies in other populations 17,19 …”
Section: Discussionsupporting
confidence: 91%
“…It is also important to note that our study replicates the findings of an increased risk of developing acute kidney injury and increased total days of hospitalization, as reported in previous studies in other populations. 17,19 We believe that the Pmsf, rather than constituting a predictor of fluid responsiveness, could constitute a limit to continue fluid resuscitation (in conjunction with other clinical tools), since there are no clinical studies to date evaluating its variation during fluid resuscitation (compared with a gold standard). Regarding the admission value (median of 18 mmHg) of the Pmsf, It is in similar ranges to those reported in studies of cardiac surgery and sepsis (9).…”
Section: Variablementioning
confidence: 99%
“…Similar to our ndings, a signi cant difference was observed, indicating that patients with RI values above 0.7 had a higher incidence of AKI. Additionally, out of the 65 patients, 23 died, and the mortality rate was signi cantly higher in patients with RI > 0.7 compared to those with RI < 0.7 (21). A systematic review conducted in 2020, similar to our research, demonstrated a signi cant difference in renal artery RI between the group with acute kidney failure and the group without kidney failure.…”
Section: Discussionsupporting
confidence: 78%
“…These medical literature points out that patients with both pathologies (DKD and COVID-19) develop multiple pathophysiological mechanisms between the lung and kidney organs. For instance, the SARS-CoV-2 infection relies on angiotensin-converting enzyme 2 as an input receptor for tubular epithelial and lung epithelial cells [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%